2021
DOI: 10.1016/j.meegid.2021.104921
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing host-viral interactome of SARS-CoV-2 for identifying vulnerable host proteins during COVID-19 pathogenesis

Abstract: The development of therapeutic targets for COVID-19 treatment relies on understanding the molecular mechanism of pathogenesis. Identifying genes and proteins involved in the infection mechanism is the key to shedding light on the complex molecular mechanisms. The combined effort of many laboratories distributed throughout the world has produced protein and genetic interactions. We integrated available results and obtained a host protein-protein interaction network composed of 1432 human proteins. Next, we perf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 82 publications
(81 reference statements)
1
26
0
Order By: Relevance
“…Previous COVID-19 studies reported that hub-high traffic genes in the brown module, such as RBX1 ( 207 210 ), PSMA3 ( 211 ), PSMA6 ( 212 ), PTEN ( 213 ), VPS29 ( 214 , 215 ), SNRPE ( 216 ), PSMA4 ( 217 ), TXN ( 218 ), PTGES3 ( 219 , 220 ), RHOA ( 57 , 221 , 222 ), CANX ( 209 ), B2M ( 223 ), GDI2 ( 57 , 224 , 225 ), TXNL1 ( 226 ), SUMO1 ( 147 , 227 , 228 ), PSMC2 ( 229 ), REEP5 ( 230 ), DECR1 ( 108 ), RAB10 ( 224 ), PRDX3 ( 231 , 232 ), ACTR2 ( 215 ), TNFSF13B ( 192 , 233 , 234 ), and ARPC3 ( 215 ), have a central role in host-SARS-COV-2 interactions. For example, ARDS and ALI in patients with severe COVID-19 were directly associated with increased expression of the PTEN and RHOA hub-high traffic genes, respectively ( 213 , 222 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous COVID-19 studies reported that hub-high traffic genes in the brown module, such as RBX1 ( 207 210 ), PSMA3 ( 211 ), PSMA6 ( 212 ), PTEN ( 213 ), VPS29 ( 214 , 215 ), SNRPE ( 216 ), PSMA4 ( 217 ), TXN ( 218 ), PTGES3 ( 219 , 220 ), RHOA ( 57 , 221 , 222 ), CANX ( 209 ), B2M ( 223 ), GDI2 ( 57 , 224 , 225 ), TXNL1 ( 226 ), SUMO1 ( 147 , 227 , 228 ), PSMC2 ( 229 ), REEP5 ( 230 ), DECR1 ( 108 ), RAB10 ( 224 ), PRDX3 ( 231 , 232 ), ACTR2 ( 215 ), TNFSF13B ( 192 , 233 , 234 ), and ARPC3 ( 215 ), have a central role in host-SARS-COV-2 interactions. For example, ARDS and ALI in patients with severe COVID-19 were directly associated with increased expression of the PTEN and RHOA hub-high traffic genes, respectively ( 213 , 222 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some of the purple module hub-high traffic genes, such as MAPK1 ( 189 , 374 ), CUL2 ( 210 ), CMTM6 ( 162 ), TXNRD1 ( 375 ), RAB1A ( 376 ), DICER1 ( 377 ), RAB5A ( 209 ), HSP90B1 ( 343 ), MAGT1 ( 378 ), ADAM10 ( 379 , 380 ), SNX2 ( 89 ), OLA1 ( 381 ), SPTLC1 ( 382 ), SH3GLB1 ( 383 ), TIMM10B ( 384 ), and CREB1 ( 385 ) hub-high traffic TF, which are central for information exchange in this module, are potential targets for development of COVID-19 therapeutic strategies. Among these, the mitogen-activated protein kinase 1 ( MAPK1 ) hub-high traffic gene is a potential core target for many anti-COVID-19 therapeutic strategies ( 189 , 374 , 386 390 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of 2019 in Wuhan (China), medical facilities reported acute pneumonia cases with an unknown origin. Further analysis revealed that a novel coronavirus, named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was responsible for that disease, subsequently called coronavirus disease 2019 (COVID-19) [11] , [20] . The clinical manifestations spanned from asymptomatic infection to severe pneumonia and a severe state of inflammation (molecularly characterised by a cytokine storm) leading to a fatal outcome [40] , [87] , [67] , [6] , [60] , [38] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, we retain that modeling the spreading using a classical SEIR (Susceptible-Exposed-Infective-Recovered) model may not be the best choice since some pa-rameters are considered at a global scale, while the spreading involves single contacts. In parallel, some previous works such as [17,18,19,20,21,22] have demonstrated that the use of a model coming from graph theory may be helpful to describe the spreading. In this way, comprehensive graphs may be derived using nodes, i.e., people, and edges, i.e., their contacts.…”
Section: Introductionmentioning
confidence: 99%